Managing hospitalized patients with bacterial infections: the price-to-pay upon site of infection - Karolina Akinosoglou; Christos Davoulos; Anne-Lise deLastic; Martha Kolosaka; Vasiliki Niarou; Spyridoula Theodoraki; Dimitrios Ziazias; Foteini Kosmopoulou; Christina- Panagiota Koutsouri; Charalambos Gogos (James Cook University, 2022)
Introduction: Infections impose a significant burden on healthcare costs worldwide. We aimed to explore antibiotic- and hospital-related costs of infections needing admission in a tertiary university hospital in Greece. Methods: We performed a prospective cohort study in the medical care unit of a tertiary university hospital in Greece, for the period May 2016 to May 2018. Patients admitted with respiratory, urinary, gastrointestinal tract, skin, soft tissue and bone infections or primary bacteremia were included in this study. Costs of hospitalization and unit cost of antibiotic regimen were retrieved from a database for Greek hospitals containing data for each International Classification of Diseases (ICD-10) code and the national formulary respectively, and manually calculated for each patient. Results: Antibiotic costs represent approximately 14-40% of total hospital-related costs depending on infection studied. Skin, soft tissue and bone infections and primary bacteremia led hospital- and antibiotic-related costs, with median costs of €6370 (interquartile range (IQR) 3330.90-11 503.90), €2519.90 (IQR 431.50-8371.10), €4418.10 (IQR 2335-8281.90) and €1394.30 (IQR 519.12-6459.90), respectively. Antibiotic- and hospital-related costs significantly differs with site of infection (p<0.0001). Length of stay is strongly correlated with antibiotic- and hospital-related costs, while site of infection is moderately related to antibiotic cost (eta value 0.445), and hospital-related cost (eta value 0.387). Conclusion: Healthcare-related costs vary substantially depending on site of infection. Information about real-life costs can drive best decisions and help to reduce healthcare expenditures.